THU0021 The analysis of PRF1, STX11, UNC13D and STXBP2 gene in systemic juvenile idiopathic arthritis with macrophage activation syndrome. (15th June 2017) - Wei, P; Zeng, H
Abstract : Objectives: We investigated the clinical characteristics of 34 cases with systemic juvenile idiopathic arthritis (SJIA) and macrophage activation syndrome (MAS) and analyzed PRF1, UNC13D, STX11 and STXBP2 gene so as to figure out the genetic pathogenic mechanism. Methods: The clinical characteristics of 34 cases with sJIA and MAS were retrospectively analyzed, and the coding sequences of PRF1, UNC13D, STX11 were amplified. DNAMAN software and NCBI BLAST were used to compare sequences. The chi-square test was employed to compare the distribution of allele and genotype frequencies between SLE patients and healthy controls. Results: Among the 34 cases, 69% were males, and the average age was 6 years. 85% (29/34 cases) of the cases underwent genetic testing and four SNPS loci were detected: PRF1 c. 1061 c > T (rs885822); UNC13D c. 659 c > T (rs3744007); STXBP2 c. 1483 T > c (rs10001) and STXBP2 c. 1616 A > G (rs6791). Compared with control group, genotype and allele frequencies of PRF1 rs885822 and STXBP2 rs10001 among the MAS cases were of significant difference (rs885822: allele frequency 2 =4.52, p=0.03; genotype frequency: 2 =5.52, p=0.02. rs10001: allele frequency 2 =21.33, p=0.00; genotype frequency: 2 =19.58, p=0.00). There were no significant differences in genotype and allele frequencies of UNC13D rs3744007 and STXBP2 rs6791 between MAS group and control group (rs3744007: allele frequency 2 =1.89, p=0.17; genotype frequency: 2 =1.59, p=0.45. rs6791: allele frequency 2 =1.69, p=0.19; genotype frequency: 2 =2.09, p=0.35). The main characteristics of the cases were persistent fever, progressive hepatosplenomegaly, a sharp decline in blood cells, effusion, significantly increased serum liver enzymes, hyperlipidemia, etc. Some children had mucosal bleeding, neurological dysfunction, etc. More than 82% children had upper respiratory tract infection before MAS onset. 90% of children had remission, while three cases developed multiple organ failure and died. Conclusions: Macrophage activation syndrome is fatal complication caused by immune imbalance. Early detection and treatment is the key to improve the prognosis. The SNP PRF1 rs885822 and STXBP2 rs1001 may be concurrent with the pathogenesis of SJIA-MAS. The SNP UNC13D rs3744007 and STXBP2 rs6791 may not play a role in SJIA-MAS. Disclosure of Interest: None declared